2019
DOI: 10.3390/coatings9110730
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Thickness of Multilayer Composite Nano-Structured Coating Ti–TiN–(Ti,Al,Si)N on the Tool Life of Metal-Cutting Tools and the Nature of Wear

Abstract: This article discusses the influence of the thickness of a nano-structured wear-resistant layer of the Ti–TiN–(Ti,Al,Si)N multilayer composite coating on its mechanical and performance properties. The study was focused on the coatings with the following thicknesses of its wear-resistant layers: 2, 3.5, 5, 7, 11, and 15 μm. The relation between the thickness of a wear-resistant layer and the time of its deposition was investigated, and the effect of the above thickness on hardness and wear resistance in scratch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Coatings 2020, 10, x FOR PEER REVIEW 5 of 17 Table 2 presents the microhardness values of the coated samples under study. All the samples under study have very close, almost equal microhardness values, and that fact correlates with the data, earlier obtained for the (Ti,Al,Si)N coating [37], and proves that the deposition time (and, correspondingly, thickness) does not significantly affect the hardness of the coating. Figure 2 presents the diffraction patterns of the coatings for Samples 1-4 under study.…”
Section: Influence Of the Coating Thickness On The Values And Nature supporting
confidence: 88%
See 3 more Smart Citations
“…Coatings 2020, 10, x FOR PEER REVIEW 5 of 17 Table 2 presents the microhardness values of the coated samples under study. All the samples under study have very close, almost equal microhardness values, and that fact correlates with the data, earlier obtained for the (Ti,Al,Si)N coating [37], and proves that the deposition time (and, correspondingly, thickness) does not significantly affect the hardness of the coating. Figure 2 presents the diffraction patterns of the coatings for Samples 1-4 under study.…”
Section: Influence Of the Coating Thickness On The Values And Nature supporting
confidence: 88%
“…To study the relation between the values of residual stress and the thickness of the coating, four samples with the Zr-ZrN-(Zr,Al,Si)N coating were manufactured with different deposition times of the wear-resistant layers of the coating with a three-layer architecture [34][35][36][37]: 15, 30, 40, and 60 min. For the deposition of coatings, a vacuum-arc VIT-2 unit was used, which was designed for the synthesis of coatings on the substrates of various tool materials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vereschak et al [ 18 ] analyzed TiN-(Ti,Al,Si)N coatings with thicknesses of 2.0, 3.5, 5.0, 7.0, 11.0 and 15.0 µm and they found that an optimal coating thickness exists for each of the different coating structures, however, it is assumed that in the case of single coatings, this range is within 2–10 µm. They also observed a sequence of internal delaminations in the case of thicker coatings.…”
Section: Introductionmentioning
confidence: 99%